ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPS KELAS V SD NEGERI NEUBOK YEE KABUPATEN NAGAN RAYA - Nurul Fadhilah; Nurmasyitah; Aida Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In Social Studies learning in Grade V at SD Negeri Neubok Yee, some students still experience difficulties in critical thinking and comprehensively understanding the learning material, which hinders the optimal achievement of Social Studies learning competencies, particularly in the topic of social interaction. This study aimed to analyze students’ critical thinking skills through the implementation of the Problem Based Learning (PBL) model in Social Studies learning for fifth-grade students at SD Negeri Neubok Yee, Nagan Raya Regency. This study employed a qualitative approach using a descriptive research design. The research subjects consisted of 24 fifth-grade students at SD Negeri Neubok Yee. Data were collected through classroom observations and a critical thinking skills test in the form of essay questions. The observation data were analyzed using descriptive percentage analysis, while the test data were analyzed through a scoring technique based on six indicators of critical thinking skills, namely interpretation, information analysis, evaluation, inference, explanation, and self-regulation. The findings revealed that the students’ critical thinking skills were generally in the fair category. The observation results indicated that the implementation of the Problem Based Learning model encouraged students to actively identify problems, participate in discussions, collaborate with their peers, express their opinions, and present the results of group discussions. The test results showed that the inference indicator obtained the highest percentage (50.00%), while the self-regulation indicator obtained the lowest percentage (38.54%). The interpretation and information analysis indicators each obtained 45.83%, the evaluation indicator obtained 48.96%, and the explanation indicator obtained 48.44%. Based on the findings, it can be concluded that students’ critical thinking skills through the implementation of the Problem Based Learning model in Social Studies learning were in the fair category. Therefore, the implementation of the Problem Based Learning model should be carried out continuously to further improve students’ critical thinking skills